The Impact of Residual Neuromuscular Blockade, Oversedation, and Hypothermia on Adverse Respiratory Events in a Postanesthetic Care Unit: A Prospective Study of Prevalence, Predictors, and Outcomes. (October 2016) - Stewart, Paul A.; Liang, Sophie S.; Li, Qiushuang Susan; Huang, Min Li; Bilgin, Ayse B.; Kim, Dukyeon; Phillips, Stephanie
Abstract : BACKGROUND: Residual neuromuscular blockade (RNMB) has been linked to adverse respiratory events (AREs) in the postanesthetic care unit (PACU). However, these events are often not attributed to RNMB by anesthesiologists because they may also be precipitated by other factors including obstructive sleep apnea, opioids, or hypnotic agents. Many anesthesiologists believe RNMB occurs infrequently and is rarely associated with adverse outcomes. This study evaluated the prevalence and predictors of RNMB and AREs. METHODS: This prospective cohort study included 599 adult patients undergoing general anesthesia who received neuromuscular blocking agents. Baseline demographic, surgical, and anesthetic variables were collected. RNMB was defined as a train-of-four ratio below 0.90 measured by electromyography on admission to the PACU. AREs were defined based on the modified Murphy's criteria. RESULTS: RNMB was present in 186 patients (31% [95% confidence interval (CI), 27%–35%]) on admission to the PACU. One or more AREs were experienced by 97 patients (16% [95% CI 13–19]). AREs were more frequent in patients with RNMB (21% vs 14%, P = .033). RNMB was significantly associated with age (adjusted relative risk [RR], 1.17 [95% CI, 1.06–1.29] per 10-year increase), type of operation (adjusted RR, 0.59 [95% CI, 0.34–0.99] for laparoscopic surgery compared with open abdominal surgery), and duration of operation (adjusted RR, 0.59 [95% CI, 0.39–0.86] for ≥90 minutes compared with <90 minutes). Using multivariate logistic regression, AREs were found to be independently associated with decreased level of consciousness (adjusted RR, 4.76 [95% CI, 1.49–6.76] for unrousable/unconscious compared with alert/awake) and lower core temperature (adjusted RR, 1.43 [95% CI, 1.04–1.92] per 1°C decrease). Although univariate analysis found a significant association between AREs and RNMB, the significance became borderline after adjusting for other covariates (adjusted RR, 1.46 [95% CI, 0.99–2.08]). CONCLUSIONS: The prevalence of RNMB in the PACU was >30%. Older age, open abdominal surgery, and duration of operation <90 minutes were associated with increased risk of RNMB in our patients. Our RR estimate for AREs was highest for depressed level of consciousness. When AREs occur in the PACU, potentially preventable causes including RNMB, hypothermia, and reduced level of consciousness should be readily identified and treated appropriately. Delaying extubation until the patient is awake and responsive may reduce AREs.